PENGARUH PUPUK ORGANIK CAIR DAN DOSIS URIN KELINCI PADA PERTUMBUHAN DAN HASIL BROCOLI - PITOYO PITOYO; TEGUH SUPRIYADI; DARYANTI DARYANTI (JURNAL ILMIAH AGRINECA, 2012)
The research was done in Selongisor village, Batur, Getasan, Semarang Regency, from May until July 2010, the type of soil is Andisol (PPT : Andosol, the altitude is 1450 metres above sea level. This research was arranged in Randomyzed Completely Block Design (RCBD) consisted of Â two tratment factors with three replications, that are ; I. rabbit urine dosage (K0 = without rabbit urine, K1 = 50 l/ha, K2 = 100 l/ha, K3 = 150 l/ha) and II. Fluid organic fertilizer dosage (O1 = 5 l/ha, O2 = 10 l/ha, O3 = 15 l/ha). The research showed that rabbit urine dosage influenced not significant to weight of fresh biomass, weight dry biomass, flower diametre, the height of plant and amount of leaves, but influence significant to the yield per block. The treatment of liquid organic fertilizer dosage showed not significant to the weight of fresh biomass, weight dry biomass, flower diametre, the height of plant and amount of leaves, and total yield of flower. Combined effect from two treatments wasÂ  not significant difference to weight of fresh biomass, weight dry biomass, flower diametre, the height of plant and amount of leaves, but influence significant to the yield per block.. The highest result is 64,167 gram get from the treatment rabbit urine dosage 150 l/ha and Fluid organic fertilizer dosage 10 l/ha.